SISTEM PENILAIAN KARYAWAN PADA PERUSAHAAN JASA BERDASARKAN PELANGGAN BERBASIS CRM (Information Technology and Telematics, 2015)
Abstrak :Employee Assessment System Based On Customer Service Company Based CRM is a system used to provide a direct assessment of the performance of employees CV.Situscom. The benefits obtained from this assessment system is the fulfillment of customer satisfaction as employee assessment based on a computerized customer well. In conducting the analysis and system design, the authors use the method of system development Waterfall. As for the system development, the authors use the method TOPSIS Algorithm. In designing the system, the authors use design tools such as UML diagram consisting of a use case diagram, sequance diagrams, and flowcharts. From this study showed that, Employee Assessment System Based Services Company Based CRM Customer has yielded data of employees based on customer ratings, so CV.SitusCom get customer loyalty. Keywords:Assessment System, Employees, Customers, CRM